A Retrospective Study Analyzing the Appropriateness of Initial Treatment of Clostridium difficile in Patients with Active Malignancy. (27th May 2018) - Fisher, Aaron; Khanal, Pradeep; Gniado, Ewa; Khaddour, Leila; Orosey, Molly; Hader, Ismail; Yadav, Siddhartha; Halalau, Alexandra
Abstract : Background . Clostridium difficile infection (CDI) is the leading cause of hospital-associated gastrointestinal illness. Previous studies reported that patients with active malignancy are at high risk for CDIs, and yet they are still classified as nonsevere CDI and initially treated with metronidazole. Our aim is to investigate the need for the escalation of antibiotic therapy in patients with CDI and active cancer treated with oral metronidazole versus oral vancomycin. Methods . This is a retrospective study of adult patients admitted with CDI and any underlying active malignancy at Beaumont Hospital, Royal Oak, Michigan, from January 2008 to December 2014. Inclusion criteria included age > 18 years old, polymerase chain reaction- (PCR-) proven CDI, and active malignancy. Results . 197 patients were included in the final analysis. 44.8% of the metronidazole group required escalation of therapy compared to 15.2% in the vancomycin group (p value = 0.001). 29.8% of the combination group (metronidazole and vancomycin) underwent deescalation of antibiotics, which was significantly higher compared to 2.2% of patients in the vancomycin group (p value < 0.001). Discussion . Our results support the initial use of vancomycin or a combination (metronidazole and vancomycin) versus metronidazole in patients with CDI and active malignancy.